Exploring Culture through Words: Developing Writing Skills for Students in Masdarling Village, Bontang City: Menggali Budaya melalui Kata: Pengembangan Keterampilan Menulis bagi Siswa dan Siswi Kampung Masdarling, Kota Bontang - Ariani, Setya; Kuncara, Singgih Daru; Nasir, Muhammad Alim Akbar; Cahyarani, Alya; Samantha, Rey Al Hendaweyah (ANDIL Mulawarman Journal of Community Engagement, 2025)
The primary objective of this community service program is to cultivate English writing skill among high school students and those living in the tourist village of Masdarling in Bontang, East Kalimantan. By connecting culture with writing experiences, the intention is to reinforce cultural identity and uphold the values of local wisdom and indigenous culture among the younger generation, particularly in light of the challenges posed by the dominance of global culture. The implementation of this community service project involves a series of stages, which include identifying the problem, planning the activity, implementing the activity, conducting evaluation and monitoring, and reporting on the activity. The culture-oriented writing outputs produced by high school students in East Kalimantan exhibit various challenges, such as a limited range of ideas, the use of complex vocabulary and grammar, and ineffective sentence construction. The findings from the community service initiatives demonstrate an increasing awareness of the significance of training for skill development. This English writing training is projected to function as a platform for local communities to enhance their ability to showcase local traditions and culture to a worldwide audience, ultimately drawing the interest of international tourists.